Kajian Fisis Radiasi Plasma Terhadap Organ Daun pada Pertumbuhan Awal Tanaman Anggrek Phalaenopsis amabilis [Physics Observation of Plasma Radiation for Leaves to Initial Growth of Phalaenopsis amabilis] - Nur, Muhammad; Setiari, Nintya; Azam, Much.; Selawanti, Ika Indah (BERKALA FISIKA, 2007)
The Phalaenopsis amabilis (â€anggrekâ€) has been irradiated by nitrogen ions for growth Â accelereting.Irradiation technique used corona plasma technology that its electrodes configuration was point-to-plan geometry to generate nitrogen ions in air. Corona glow discharge Plasma has been generated by DC Voltage of 3.50 kV and current was 0,23 mA.Â Nitrogem ions that were irradiated to Phalaenopsis amabilis (â€anggrekâ€) have been bombarded toÂ leaf organ during 1 toÂ 7 minutes. We used two types Phalaenopsis amabilis control:Â control with fertilizer and control without fertilizer. Growing of Phalaenopsis amabilisÂ can be accellereted about 90 % compare with control withoutÂ fertilizer and 30 % compare with control with fertilzer. The maximum growing of Phalaenopsis amabilis by using plasma technology for time irradiation of 1 or 2 minutes. Â Key wordsÂ : corona glow discharge plasma, Phalaenopsis amabilis (anggrek), nitrogen, ion electrons,Â free radicals.